Checkpoint antibody receptor modified ARMed CAR T circumvents the suppressive immunome in GBM - Cook, Danielle R.; Boesteanu, Alina C.; Yin, Yibo; Reid, Reiss; Roccograndi, Laura; Dahmane, Nadia; Martinez-Lage, Maria; O’Rourke, Donald M.; June, Carl H.; Johnson, Laura A. (Frontiers in Immunology, 2025)
IntroductionGlioblastoma (GBM) remains a deadly cancer with non-curative upfront treatment of radiation, resection, and chemotherapy. Not only has the standard of care for GBM patients not improved significantly over the past decade, life expectancy is less than 18 months, with no standard second-line therapy. We previously developed a 2nd generation 4-1BB co-stimulated chimeric antigen receptor (CAR) targeting tumor-specific variant of the epidermal growth factor receptor (EGFRvIII) for treating patients with GBM. This CAR T was used in Phase 1 clinical trials, and demonstrated that CAR T cells rapidly trafficked to tumors and showed initial anti-tumor activity upon encountering EGFRvIII-bearing tumor cells. However, the CAR T cells rapidly became exhausted, losing anti-tumor function, with no durable objective tumor responses.MethodsHere, we evaluated the GBM immune environment in a syngeneic implantable GL261 murine model. Prior to tumor implantation, brain-resident immune cells were mostly absent. Following tumor engraftment, there was a pronounced increase in immune cell infiltration over time and with GBM size. Immune infiltrates were intitally comprised of early-arriving lymphocytes including T, NK, and B cells, later this shifted towards increased presence of macrophages and myeloid-derived suppressor cells. Evaluating both fresh and archival GBM samples from patients, we found similarly high levels of infiltrating immune cells, and PDL1 expression on both tumor and immune cells. PD1/PDL1-antibody (Ab) mediated checkpoint inhibition (CPI) has been transformative in treating several types of solid tumors; however the localization of GBM behind the blood-brain barrier limits Ab access, and CPI trials have been unsuccessful in treating GBM. To deliver PD1/PDL1 checkpoint Ab for patients with GBM, we engineered our EGFRvIII-targeted CAR T cells to function as bio-factories, producing and secreting anti-PD1 mini-Abs in situ at the site of GBM.ResultsThese Ab receptor-modified (ARMed) CAR T cells produced functional PD1 minibodies in vitro and demonstrated anti-tumor activity in vivo in a GBM xenograft model using NOD-Scid gammaC-null (NSG) mice. Delivered systemically, both soluble Ab plus CAR T, and ARMed CAR T cells improved subcutaneously implanted GBM treatment over CAR T alone, while treatment of orthotopic GBM treatment was only improved with ARMed CAR T therapy.DiscussionThese findings demonstrate that engineering EGFRvIII-directed CAR T cells to secrete checkpoint inhibitors locally can overcome immunosuppressive barriers in GBM and bypass the limitations of systemic antibody delivery. This strategy enhances CAR T cell functional persistence and holds strong translational potential for treating GBM and other CNS-localized disease.